2015
DOI: 10.1148/radiol.14140221
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal In-Bore 3-T MR Imaging–guided Prostate Biopsy: A Prospective Clinical Observational Study

Abstract: The contents of this manuscript are solely the responsibility of the authors and do not necessarily represent the official views of the National Institutes of Health.q RSNA, 2014 Purpose:To determine the detection rate, clinical relevance, Gleason grade, and location of prostate cancer (PCa) diagnosed with and the safety of an in-bore transperineal 3-T magnetic resonance (MR) imaging-guided prostate biopsy in a clinically heterogeneous patient population. Materials and Methods:This prospective retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 48 publications
2
78
1
1
Order By: Relevance
“…However, in a biopsy-based multivariable analysis, the repeat biopsy procedure itself was not associated with a greater risk of serious complications requiring hospital admission compared to the initial biopsy session 59 . In patients undergoing transperineal PB, the reported incidence of infections and sepsis is close to zero (0-0.2%), given the avoidance of bacterial contamination (which is common during transrectal access), as well as the limited number of cores taken when performing transperineal MRI-guided in bore biopsy [8][9][10]13,[25][26][27]29,[63][64][65][66][67] . Although data are currently limited, it is uncertain whether the lower incidence of infectious complications after MRI-targeted PB could be related to the sampling route (i.e.…”
Section: Infectious Complications and Hospitalization Rates After Promentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a biopsy-based multivariable analysis, the repeat biopsy procedure itself was not associated with a greater risk of serious complications requiring hospital admission compared to the initial biopsy session 59 . In patients undergoing transperineal PB, the reported incidence of infections and sepsis is close to zero (0-0.2%), given the avoidance of bacterial contamination (which is common during transrectal access), as well as the limited number of cores taken when performing transperineal MRI-guided in bore biopsy [8][9][10]13,[25][26][27]29,[63][64][65][66][67] . Although data are currently limited, it is uncertain whether the lower incidence of infectious complications after MRI-targeted PB could be related to the sampling route (i.e.…”
Section: Infectious Complications and Hospitalization Rates After Promentioning
confidence: 99%
“…In a comparative series of patients undergoing transrectal MRI-targeted PB and TRUS-guided PB, the Authors found a lower incidence of infective complications in the former group (the rate of infections was halved compared to the latter), even if not statistically significant 14 . Conversely, the infectious complication rate after in-bore transperineal MRI-targeted biopsy appears virtually absent, with a hospitalization rate of 0% 29,64 .A minority of patients require hospitalization for the management of serious biopsy-related adverse events or the exacerbation of underlying medical conditions. Data on hospital admissions following PB were recently reported by Anastadiasis et al from the English national cancer registry 58 .…”
Section: Infectious Complications and Hospitalization Rates After Promentioning
confidence: 99%
See 1 more Smart Citation
“…• Fusion-биопсия имеет высокую эффективность при обнаружении опухолей передней зоны ПЖ, которые при классическом подходе не диагности-руются в 77 % случаев [14].…”
Section: Introductionunclassified
“…Software such as 3Dslicer (www .slicer.org) efficiently registers/fuses previously acquired mpMRI data on intraprocedural images and improves the accuracy of the biopsy targeting. 47 Focal ablative therapies use image guidance to ablate focal areas of prostate cancer within the gland with either heat (laser, high-frequency ultrasound) or cold temperature (cryo), and can be used to treat localized prostate cancer. mpMRI is the most reliable modality for image-guided focal therapies because of its high spatial resolution and accurate tumor detection.…”
mentioning
confidence: 99%